Three new species in the leafhopper genus Angustuma (Hemiptera: Cicadellidae: Evacanthinae) from Thailand - Wang, Yang; Zhang, Yalin (Zootaxa, 2014)
The genus Angustuma Xing & Li, 2013 of the subfamily Evacanthinae is recorded from Thailand for the first time. Three new species, Angustuma basinigra sp. nov., Angustuma flavinigra sp. nov. and Angustuma flavimacula sp. nov., are described and illustrated. Their diagnostic characteristics are compared with close relatives. A key to all known species of Angustuma is provided.